The Amplitude and Timescales of 0‐15 ka Paleomagnetic Secular Variation in the Northern North Atlantic - Reilly, Brendan T.; Stoner, Joseph S.; Ólafsdóttir, Sædís; Jennings, Anne; Hatfield, Robert; Kristjánsdóttir, Gréta Björk; Geirsdóttir, Áslaug (Journal of Geophysical Research: Solid Earth, 2023)
We investigate the amplitude and frequency of directional geomagnetic change since 15 ka in the Northern North Atlantic (∼67o N) using 5 ‘ultra-high’ resolution continental shelf sediment cores deposited at rates greater than 1 m/kyr. The ages of these cores are constrained by 103 radiocarbon dates with reservoir ages assessed through tephra correlation to terrestrial archives. Our study aims to address many of the uncertainties that are common in sedimentary paleomagnetic studies, including signal attenuation in low to moderate resolution archives and difficulty to demonstrate reproducibility in higher resolution archives. The ‘ultra-high’ accumulation rates of our cores reduce ‘lock-in’ and smoothing uncertainties associated with magnetic acquisition processes. Abundant radiocarbon dates along with an objective alignment algorithm provide a test of signal reproducibility at sub-millennial timescales. The PSV signal, evaluated as individual records and as a new stack (GREENICE15k), validates prior results, but provides stronger geochronological constraints, demonstrates a reproducible PSV signal and amplitude, and extends through the abrupt Bølling–Allerød and Younger Dryas climate transitions of the latest Pleistocene. While broadly consistent with time-varying spherical harmonic models and varve dated records from Northern Europe, we demonstrate greater variance and higher amplitudes—particularly at sub-millennial timescales. This robust variability on centennial timescales is rarely observed or discussed, but is likely important to our understanding of some of the most intriguing aspects of the geodynamo. Key Points Sediment cores with ultra-high accumulation rates are used to study directional changes in the Northern North Atlantic’s geomagnetic field Study addresses uncertainties in sedimentary paleomagnetic research, such as signal attenuation, chronology, and reproducibility Study reveals robust variability on centennial timescales with greater variance than generally observed over the last 15,000 years ...